Métodos de Contagem - Bezerra, Luis Rodrigo D'Andrada (2013)
This paper presents an introduction to the study of counting problems, not just through the concepts traditionally covered in Combinatorial Analysis courses, such as the basic principles, permutations, arrangements, combinations, linear equations with unitary coe cients, among others, but also using sophisticated tools, such as the use of graphs.